A novel polyurethane/cellulose fibrous scaffold for cardiac tissue engineering. Issue 9 (24th December 2014) - Chen, Po-Hsuen; Liao, Hsueh-Chung; Hsu, Sheng-Hao; Chen, Rung-Shu; Wu, Ming-Chung; Yang, Yi-Fan; Wu, Chau-Chung; Chen, Min-Huey; Su, Wei-Fang
Abstract : A high mechanical strength and biomimetic scaffold is electrospun from a blend of polyurethane and ethyl cellulose, being promising in applications for therapeutic purposes as a cardiac graft for reconstructing or regeneration of damaged myocardium. Abstract : The present work demonstrates a biomimetic electrospun scaffold based on polyurethane (PU) and ethyl cellulose (EC), featuring uniform fibrous nanostructures and three dimensional porous networks. The relationship between processing conditions and fibrous nanostructures is established which guides the rational processing with tunable fiber diameters. Additionally, the developed scaffold template reveals biocompatibility in retention and proliferation of cardiac myoblast H9C2 cells. The high mechanical strength of the PU/EC scaffolds enables the processing and handling of an ultrathin patch. Their elastomeric characteristics revealed the compatibility between the patch and contractile tissues. Furthermore, anisotropic PU/EC scaffolds with aligned nanofibers were successfully fabricated, exhibiting higher mechanical strength and essential characteristics for the survival and function of cardiac cells with native anisotropy. This work demonstrates a bioengineered PU/EC fibrous scaffold with uniform nanostructural webs and provides insight into the relationships between processing control, nanostructures and associated properties, with promising potential in cardiac tissue engineering.